2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626248
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of smooth muscle cells' shape and proliferation rate in novel short-term thermal angioplasty ex vivo and in vitro

Abstract: We investigated the influences on the smooth muscle cells of temporally heated arterial walls in both ex vivo and in vitro study to determine the optimum heat parameter of novel short-term thermal angioplasty, Photo-thermo Dynamic Balloon Angioplasty (PTDBA). Arterial heating dilatation was performed by the prototype PTDBA balloon ex vivo. We found that the smooth muscle cells in the vessel wall were stretch-fixed after the heating dilatation ex vivo. The stretch-fixing rate of these cells was increased with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In our previous ex vivo study, we revealed that the smooth muscle cells were fixed in the stretched shape after PTDBA ( Figure 1) [15]. In this study, we examined the cell proliferation rate of the stretch-fixed smooth muscle cells in vitro, measured the deformation rate of the smooth muscle cells after PTDBA in vivo, and focused on the distribution of the smooth muscle cells' growth factor and its receptor in vivo.…”
Section: Introductionmentioning
confidence: 97%
“…In our previous ex vivo study, we revealed that the smooth muscle cells were fixed in the stretched shape after PTDBA ( Figure 1) [15]. In this study, we examined the cell proliferation rate of the stretch-fixed smooth muscle cells in vitro, measured the deformation rate of the smooth muscle cells after PTDBA in vivo, and focused on the distribution of the smooth muscle cells' growth factor and its receptor in vivo.…”
Section: Introductionmentioning
confidence: 97%